Factors associated with maternal choice to provide breast milk for low birthweight infants. Issue 1 (January 1988) - Lucas, A; Cole, T J; Morley, R; Lucas, P J; Davis, J A; Bamford, M F; Crowle, P; Dossetor, J F; Pearse, R; Boon, A
Abstract : Factors associated with maternal choice to provide milk for premature infants were investigated in 925 mother/infant pairs in five hospitals. A well educated, married, primiparous mother aged 20 or over who delivered a baby boy by caesarean section was nearly 1000 times more likely to choose to express her milk than a mother who was poorly educated, single, multiparous, and aged under 20, delivering a female infant vaginally. Evidence from the five centres suggested that hospital staff have little influence on a mother's choice of feeding method. The major differences between the populations of babies whose mothers do or do not choose to provide milk, raise important issues concerning the interpretation of data from non-randomised clinical trials of feeding premature infants.